Alternative dispute resolution: definition and its development - Ansari, Abdul Haseeb; Ahmad, Muhamad Hassan; Yaakob, Adnan (CLJ Publication, 2020)
When consensus fails, disputes are more likely to occur. It is thus, an unpleasant reflection of uncompromising or obdurate human nature. Peaceful reconciliation is always the first choice, but it may not be all that successful in economic, financial and property-related disputes. For example, disputes in banking and finance, including Islamic banking and finance, are relatively more noticeable, in spite of the efforts of the players to minimise conflict situations by arranging steps to prevent disputes from arising, and prescribing procedures for dispensing fast and amicable resolutions so that they finally settle down. The choice of modes of settlements, contentious or alternative dispute resolution (ADR), are based on the choice and circumstances of disputing parties. However, due to certain obvious reasons, ADR mechanisms are gaining preference over recourse to the court system at both national and international levels. Among the three popular methods of ADR, arbitration, mediation and conciliation, arbitration is usually preferred, with or without the preceding stages of mediation or conciliation. But for logical and practical reasons, mediation, where the mediator acts as a facilitator and the disputing parties have relatively more say, should be the first method of ADR to be resorted to; and it should be followed by conciliation, where the conciliator himself draws proposals of settlement or formulates or re-formulates the terms of settlement as a reasonable compromise solution to the dispute. A conciliator may also persuade the parties to the proposed settlement. Arbitration, from the point of view of resolving a dispute without any external interference, should supposedly be the last choice. But in a good number of cases, it is a preferred choice, when consensus fails, a third party has to come in as an arbitrator on mutual consent basis to resolve the dispute. It is evident that for various reasons, arbitration is taking preference over the judicial system, both nationally and internationally, especially in commercial, banking and construction-related disputes. It may be noted here that the role of arbitration in banking and finance and building construction sector, is relatively more significant than other sectors. In resolving personal law disputes, like those relating to marriage, divorce, succession, guardianship, succession, maintenance and adoption, negotiation and conciliation, are usually the preferred means of settling disputes. ADR mechanisms have less value in hard cases where parties to disputes lack flexibility and have trust only in court-centered dispute resolution no matter how much time and money they would have spent. There are innumerable instances where cases have run through generations, proving to be both costly and time-consuming and in many complex cases, decisions would have been made after the death of the litigants. The phrase ‘justice delayed is justice denied’ is very true in many of contentious cases resolved by the court system. ADR mechanisms have been practised in various parts of the world and may even date back to 1800 BC. They are also accentuated and preferred in Islam and other popular religions of the world. They have now been well accepted as amicable, fast and inexpensive processes of dispute resolution both at national and international levels. In many countries, quasi-judicial bodies under tax laws and labour laws are attempting to resolve disputes mainly via ADR mechanisms, and tribunals/courts, when parties are not satisfied with the resolution/ awards of administrative authorities. At the international level, other than the International Court of Arbitration and regional arbitration centres; the Dispute Settlement Body (DSB) of the World Trade Organization, the International Court of Justice, the International Tribunal for the Law of the Sea (ITLOS) and the World Intellectual Property Organization (WIPO), invariably resort to ADR mechanisms in their decisions and reports. Often disputing states are asked to resolve their disputes on the basis of conciliation or mediation. This chapter will first discuss the concept, benefits and disadvantages. It will then shed some light on various means of ADR mechanisms and their development.